Digital Printing of Enzymes on Textile Substrates as Functional Materials (Journal of Fiber Bioengineering and Informatics, 2014)
Recently, there have been significant developments in inkjet printing for applications in various fieldssuch as medicine, biomaterials and sensors. In this research, enzymes like horseradish peroxidase (HRP)and glucose oxidase (GOx) were directly printed by inkjet printer onto flexible textile fabric in predefinedpatterns to produce a functional material. The functionality of the printed enzymes (bioink) wasinvestigated by chemical reaction after printing fresh and stored bio-ink in a digital printer. The resultsindicated that these enzymes can be effectively printed individually or in combination, which retainstheir functionality after printing. Furthermore, HRP was coupled and printed with fluorescent group,the result confirmed that the printed enzyme was still active and retained its functionality despite theprinting process. Hence, the digital printing technique can be used as a novel method for producingfunctional textiles for advanced applications in monitoring health and security.